Are boys discriminated in Swedish high schools? - Björn Tyrefors Hinnerich; Erik Höglin; Magnus Johannesson (Institute for Labour Market Policy Evaluation (IFAU), 2010)
Girls typically have higher grades than boys in school and recent research suggests that part of this gender difference may be due to discrimination of boys. We rigorously test this in a field experiment where a random sample of the same tests in the Swedish language is subject to blind and non-blind grading. The non-blind test score is on average 15 % lower for boys than for girls. Blind grading lowers the average grades with 13 %, indicating that personal ties and/or grade inflation are important in non-blind grading. But we find no evidence of discrimination against boys. The point estimate of the discrimination effect is close to zero with a 95 % confidence interval of ±4.5 % of the average non-blind grade.
Keywords: C93; I20; J16; 330; discrimination; field experiments; grading; education; gender